Original Approach for Automated Quantification of Antinuclear Autoantibodies by Indirect Immunofluorescence - Daniel Bertin; Noémie Jourde-Chiche; Pierre Bongrand; Nathalie Bardin (Clinical and Developmental Immunology)
Introduction. Indirect immunofluorescence (IIF) is the gold standard method for the detection of antinuclear antibodies (ANA) which are essential markers for the diagnosis of systemic autoimmune rheumatic diseases. For the discrimination of positive and negative samples, we propose here an original approach named Immunofluorescence for Computed Antinuclear antibody Rational Evaluation (ICARE) based on the calculation of a fluorescence index (FI). Methods. We made comparison between FI and visual evaluations on 237 consecutive samples and on a cohort of 25 patients with SLE. Results. We obtained very good technical performance of FI (95% sensitivity, 98% specificity, and a kappa of 0.92), even in a subgroup of weakly positive samples. A significant correlation between quantification of FI and IIF ANA titers was found (Spearman's ρ=0.80, P<0.0001). Clinical performance of ICARE was validated on a cohort of patients with SLE corroborating the fact that FI could represent an attractive alternative for the evaluation of antibody titer. Conclusion. Our results represent a major step for automated quantification of IIF ANA, opening attractive perspectives such as rapid sample screening and laboratory standardization.